RANCANGAN KEY PERFORMANCE INDICATOR (KPI) DIVISI HUMAN CAPITAL DAN AKUNTANSI & KEUANGAN RUMAH SAKIT UNPAD DENGAN PENDEKATAN BALANCED SCORECARD (BSC) - Fayza Fauziah; Wa Ode Zusnita Muizu (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2025)
This study aims to provide an overview of the current performance measurement model, design Key Performance Indicators (KPIs) using the Balanced Scorecard (BSC) approach, and develop a comprehensive performance measurement model for the Human Capital Division and the Accounting & Finance Division of RS UNPAD. The research employs a descriptive qualitative method, with data collected through interviews, observations, documentation, and literature review. Data analysis is conducted using the Miles and Huberman model, which includes the stages of data reduction, data display, and conclusion drawing. The findings reveal that: (1) the current performance measurement at RS UNPAD is still simple, manual, and lacks a standardized KPI structure; (2) the proposed KPIs are aligned with the organization’s strategic objectives and the job descriptions of each position; and (3) the proposed performance measurement model for the Human Capital and Accounting & Finance Divisions consists of an individual KPI evaluation system developed through a cascading process from the organizational level down to staff level. The indicators are based on the Balanced Scorecard (BSC) framework and job descriptions, and are periodically evaluated by the Human Capital Team through a series of stages that serve as the foundation for managerial decision making.